Strengthening in microbiota dynamics and C, N, S transformation induced by novel synthesized pyrite/PHBV composites for advanced nitrogen and phosphate removal: Overlooked sulfate reduction process - Qi Zhou; Jia, Lixia; Li, Yuanwei; Wu, Weizhong (CHEMICAL ENGINEERING JOURNAL, 2023)
Fine-grained pyrites are difficult to be denitrified under natural environment due to chemical oxidation with O2. In this study, the pyrite/PHBV composites were synthesized through high-temperature melting and realized nitrogen and phosphate removal under natural aerobic conditions. Results showed that pyrite/PHBV-40 composites had the highest denitrification rate of 0.61 mg NO3–N /(LCh) with low SO42-production, and its removal efficiency of nitrogen and phosphorus was 98% and 41%, respectively. Microbial community structure analysis revealed that the enrich sulfate-reducing bacteria (SRB) on the pyrite/PHBV-40 composites demonstrated that the sulfate reduction driven by SRB enhanced denitrification process, and thereby the S cycle could underpin the potential self-sustainability of pyrite/PHBV-40 composites. Co-occurrence network analysis showed that Fe oxidizers/reducers (e.g., Ferruginibacter/Geobacter) and SRB (e.g., Desulfovibrio) were the keystone species in microbial community. Bugbase analysis showed that formed biofilms mainly consisted of aerobic and facultative anaerobic strains, which was corresponding to structure of biofilm including aerobic and anoxic layer. Partial mantel test revealed the total Fe and nutrients (e.g., N and P) are the drivers in OTU and phenotype composition, respectively. Metabolic pathway analysis suggested that pyrite/PHBV composites may not only accelerate glycolysis with rapid hydrolysis of PHBV, but also enhance the TCA cycle with high production of ATP and NADH. The final product of nitrate reduction is N2O or NO, and the cysJ gene play an important role in sulfate reduction in pyrite/PHBV systems. Overall, the novel synthesized pyrite/PHBV composites are an ideal functional material with high denitrification rate, no secondary pollution and long service life. Our study highlights pyrite/PHBV-induced strength in microbiota dynamics and C, N, S transformation, therein, the sulfate reduction process cannot be overlooked.